Abordaje fisioterapéutico y su incidencia en la lesión del ligamento cruzado anterior en los deportistas que acuden a la Federación Deportiva de Los Ríos del cantón Babahoyo en el periodo junio - septiembre 2024. - Gastesi Rivera, Jamileth Andreina (2024)
The present study addresses the incidence and treatment of ACL injury in athletes who attend the Los Ríos Sports Federation in Babahoyo. The ligament provides stability in the knee and this injury, which is common in high-intensity sports, can significantly increase the occurrence of said injury among athletes. Some factors include age, level of physical activity, and severity of the injury. . . The research emphasizes how an adequate and personalized physiotherapeutic approach can intervene in their recovery and prevent future injuries, thus developing a focus on rehabilitation techniques and biomechanical education such as strengthening exercises, joint mobility and the use of manual therapies which are combined for a better recovery process. Additionally, the project highlights the important role of patient education in their recovery process, through a multidisciplinary approach that introduces physiotherapists, trainers and doctors. Finally, this study includes interviews with Federation physiotherapists who offered perspectives on the application of these methods in clinical practice, reinforcing the relevance of the personalized and evidence-based approach to the complete recovery of athletes with ACL injury.